THE MODIGLIANI–ADDO–BRUMBERG LIFE-CYCLE MODEL: APPLYING TO UKRAINE’S ECONOMY - Bazhenova, Olena V.; Krytsun, Kateryna I. (Ekonomika, 2013)
Abstract. The authors investigate and analyze the possibility of the Modigliani–Ando–Brumberg life-cycle model to describe the relationship among income, consumption, savings, and inheritance of individual households of Ukraine’s economy by using the state statistics data of Ukraine. The features and contradictions of the assumption that a person has the desire to stabilize consumption and make it uniform throughout his life to Ukrainian households are tested. Key words: life cycle model, savings, income, debt, retirement, consumption, wealth, inheritance, constant consumption